2020
DOI: 10.1038/s41598-020-71588-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mycobacteriophage toxic genes reveals new features of mycobacterial physiology and morphology

Abstract: Double-stranded DNA tailed bacteriophages typically code for 50-200 genes, of which 15-35 are involved in virion structure and assembly, DNA packaging, lysis, and DNA metabolism. However, vast numbers of other phage genes are small, are not required for lytic growth, and are of unknown function. The 1,885 sequenced mycobacteriophages encompass over 200,000 genes in 7,300 distinct protein 'phamilies', 77% of which are of unknown function. Gene toxicity provides potential insights into function, and here we scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…It is likely that phage genes play important roles not just in host range determination, but in other aspects of viral dynamics, including out-competing other phages in lytic growth. Several studies have shown that a substantial proportion (approximately 20%) of phage genes are toxic to the host cell when expressed alone [ 82 , 83 ]. This toxicity itself is likely immaterial to lytic phage growth, as the cell is going to die anyway, and we suggest it more commonly derives from inactivation of cell processes that other phages depend on to lytically infect the bacterium.…”
Section: Mycobacteriophages Are Viruses Of Mycobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that phage genes play important roles not just in host range determination, but in other aspects of viral dynamics, including out-competing other phages in lytic growth. Several studies have shown that a substantial proportion (approximately 20%) of phage genes are toxic to the host cell when expressed alone [ 82 , 83 ]. This toxicity itself is likely immaterial to lytic phage growth, as the cell is going to die anyway, and we suggest it more commonly derives from inactivation of cell processes that other phages depend on to lytically infect the bacterium.…”
Section: Mycobacteriophages Are Viruses Of Mycobacteriamentioning
confidence: 99%
“…An unrelated phage, Rosebush, requires DivIVA to infect, and is therefore excluded from Fruitloop-infected cells by this mechanism [ 82 ]. It seems likely that other genes identified as toxic are involved in similar processes [ 83 ].…”
Section: Mycobacteriophages Are Viruses Of Mycobacteriamentioning
confidence: 99%
“…In this case, YIP was discovered by a growth inhibition screen [ 209 ]. Similarly, Ko and Hatfull (2020) screened 193 diverse mycobacteriophage genes from 13 different genomes and found that about 23% of them were toxic when expressed in Mycobacterium smegmatis [ 210 ]; this set of phage ORFans could easily be queried for biofilm impact.…”
Section: The Search For Undiscovered Bacteriophage Antibiofilm Mechan...mentioning
confidence: 99%
“…Other non-structural genes are tRNA and tmRNA, potentially involved in gene expression [ 80 , 83 ], mobile genetic elements (MGEs) [ 84 , 85 ], and several other genes of unknown function [ 55 ]. The latter do not seem to be required directly for phage replication, but instead might modulate bacteria-phage and/or phage-phage dynamic interactions [ 86 , 87 ]. Indeed, temperate mycobacteriophages, which can either undergo lytic or lysogenic cycle ( Figure 1 A), play important roles in these interactions both during lysogeny by prophage-mediated defense systems against the attack of other phages, and by superinfection exclusion during lytic replication, reviewed in detail elsewhere [ 77 , 88 , 89 , 90 ].…”
Section: Mycobacteriophagesmentioning
confidence: 99%